2006
DOI: 10.1097/01.fpc.0000184953.31324.e4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intestinal CYP3A5 on postoperative tacrolimus trough levels in living-donor liver transplant recipients

Abstract: It has been reported that hepatic and intestinal cytochrome P450 (CYP) 3A4, CYP3A5 and P-glycoprotein affect the pharmacokinetics of tacrolimus, and that these proteins are associated with the large inter-individual variation in the pharmacokinetics of this drug. We previously showed that the concentration/dose ratio of tacrolimus tended to be lower in recipients of living-donor liver transplantation (LDLT) with a CYP3A5*1/*1-carrying graft. However, the effect of intestinal CYP3A5 remains to be elucidated. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 29 publications
(46 reference statements)
12
90
0
Order By: Relevance
“…29 CYP3A5*1 carrier state is associated with higher hepatic and intestinal CYP3A5 expression and activity, [30][31][32][33] thus in CYP3A5 expressers, more diltiazme N-demethylation metabolites are formed resulting in stronger inhibition of CYP3A activity, which might explain the finding of our study. In addition, in recent years, expression of CYP3A enzyme has been shown to be transcriptionally regulated by nuclear receptor pregnane X receptor (PXR).…”
Section: Cyp3a5*3 and Diltiazem-tacrolimus Interactionsupporting
confidence: 77%
“…29 CYP3A5*1 carrier state is associated with higher hepatic and intestinal CYP3A5 expression and activity, [30][31][32][33] thus in CYP3A5 expressers, more diltiazme N-demethylation metabolites are formed resulting in stronger inhibition of CYP3A activity, which might explain the finding of our study. In addition, in recent years, expression of CYP3A enzyme has been shown to be transcriptionally regulated by nuclear receptor pregnane X receptor (PXR).…”
Section: Cyp3a5*3 and Diltiazem-tacrolimus Interactionsupporting
confidence: 77%
“…Previously, we showed that the cytochrome P450 (CYP) CYP3A5*1 allele not only in the liver (donor genotype) but also in the small intestine (recipient genotype) achieved lower concentration/dose (C/D) ratio of tacrolimus than that with CYP3A5*3 (rs776746)/*3 homozygotes in living-donor liver transplant patients. [3][4][5][6] Recently, a new SNP in the CYP3A4 gene, CYP3A4*1G in intron 10, has been found in human lymphoblastoid cell lines from different ethnic groups and is the most common SNP in Japanese patients. 7,8) Miura et al 9) reported that dose-adjusted area under the concentration-time curve and trough level of tacrolimus in renal transplant patients with CYP3A4*1G/*1G was lower than those in patients with CYP3A4*1/*1.…”
Section: Influence Of Cytochrome P450 (Cyp)mentioning
confidence: 99%
“…The CYP3A5*3 was detected using the polymerase chain reaction (PCR)-restriction fragment length polymorphism method as described previously. 6) We genotyped the CYP3A4*1G using Taqman ® Drug Metabolism Assays (catalogue number: C_26201900_30, Applied Biosystems, Foster, California, U.S.A.). PCR was performed according to the manufacturer's instructions using StepOnePlus Real-Time PCR System (Applied Biosystems).…”
Section: Measurement Of Tacrolimus Concentrationsmentioning
confidence: 99%
“…A significant difference in tacrolimus daily dose and C/D ratios has also been reported between recipients with the CYP3A5 6986GG allele and those with the CYP3A5 6986AG/AA allele within 6 months of transplantation (Provenzani et al, 2011). A previous study also found that the genetic polymorphism of intestinal CYP3A5 in liver transplant patients was an important factor affecting tacrolimus blood concentration (Uesugi et al, 2006).…”
Section: Discussionmentioning
confidence: 87%